CP-057 Partial economic evaluation of pharmaceutical interventions on the prescription of direct oral anticoagulants in a teaching hospital. (14th February 2016) - Declaye, C; Sennesael, AL; Larock, AS; Spinewine, A; Hecq, JD; Krug, B
Abstract : Background: Direct oral anticoagulants (DOAC) are widely used in patients with atrial fibrillation. However, inappropriate use is prevalent, and this potentially increases the risk of thromboembolic and haemorrhagic events. These events also imply an important economic burden. In our institution, a clinical pharmacist is dedicated to performing medication review for all DOAC patients. Purpose: To determine the net cost avoidance of pharmaceutical interventions on the DOAC prescription. Material and methods: We constructed a decision tree model, using a public payer perspective. We included hospitalised medical patients taking a DOAC. The appropriateness of the prescription was assessed using nine items of the Medication Appropriatenes Index 1 . The theoretical thromboembolic and haemorrhagic risks of patients under DOAC were collected from the literature. Evaluation of the individual potential risks was based on the Nesbit risk assignment conducted by two independent clinical pharmacists 2 . Based on diagnosis related group coding and literature data, different costs were included: institutional disease costs of complications, annualised ambulatory stroke costs, drugs costs and pharmacist costs. In the reference case we did not add consultancy fees for the pharmacist. A univariate sensitivity analysis was performed to evaluate the robustness of our results and key assumptions. Results: 75 patients met the inclusion criteria. 36 (48%) had an inappropriate DOAC prescription. The net cost benefit analysis showed that the saved difference between avoided costs (7954€) and annualised medication costs and pharmacist costs (4 323€) was 3631€ for 75 patients. The univariate sensitivity analysis enlightened a net cost benefit if the prevalence of inappropriate prescribing and disease costs decreased to 28% and 45%, respectively. Conclusion: Besides enhancement of the prescription's quality by the clinical pharmacist, our results provide evidence that this intervention brings positive economic benefits. A complete economic analysis should be considered to demonstrate the cost effectiveness of a clinical pharmacist. References and/or Acknowledgements: Larock AS, et al . Appropriateness of prescribing dabigatran etexilate and rivaroxaban in patients with nonvalvular atrial fibrillation: a prospective study, Ann Pharmacother 2014;48:1258 Nesbit, et al . Implementation and pharmacoeconomic analysis of a clinical staff pharmacist practice model, Am J Health Syst Pharm 2001;58:784 No conflict of interest.